Pollution assessment and source approximation of trace elements in the farmland soil near the trafficway - Sun, Linhua (Journal of Environmental Engineering and Landscape Management, 2020)
The traffic related environmental pollution problems have attracted a lot of attention. In this study, contents of eight trace elements along with Fe and Mn in the farmland soil near a trafficway of Suzhou, Anhui province, China have been measured for the pollution assessment and source identification (along with quantification). The results show that iron is the most abundant element, followed by manganese, zinc, chromium, nickel, copper, lead, arsenic, cobalt and cadmium. They have coefficients of variation range between 0.028 and 0.281, indicating that some of them might have multi-sources. The pollution indexes (including single pollution, geo-accumulation and the Nemerow composite indexes) indicate that the soil samples are slightly polluted. Multivariate statistical analyses (including correlation, cluster and factor analyses) have identified three sources (geogenic, traffic and agriculture related) responsible for the elemental concentrations in the soils. Moreover, the EPA Unmix model have calculated their mean contributions to be 33.4%, 33.2% and 33.3%, respectively.